حساب عناصر أمواج الرياح أمام شاطئ اللاذقية - عدنان ابراهيم; دانا البني (Tishreen University, 2018)
The study of wave's systems in open water (deep water) in front of the shore of any coastal countries is considered a very important issue for building and improving the ports and different coastal constructions. The study of the waves systems is started from the climate data recorded in the study area and along adjacent marine areas, including the dominating winds directions, intensity, and the time of storms affecting, in addition to studying the dominant geographical and topographical status of the coastline and studied sea water area.  The so -called wave field for an area will help to build a field data base for the waves systems which provide the data base with new and continuous records on the waves systems. We will depend on this data in field studies, coastal designing and construction. A mathematical model of the wave field formed in the region was built using the Surface Water Modeling System (SMS) model (ADCIRC-STWAVE). This model has contributed to the development of a map of the waves and currents formed within a period of 50 years for the prevailing winds in the region. The results of this model can be adopted because of its accuracy and reliability. تعتبر دراسة منظومة الأمواج في المياه المفتوحة أمام شواطئ أي بلد ساحلي مسألة بغاية الأهمية من أجل عملية بناء وتطوير المرافئ ومختلف المنشآت الشاطئية. تنطلق دراسة منظومة الأمواج المسيطرة من المعطيات المناخية المسجلة في منطقة الدراسة وامتداد المسطحات المائية البحرية المجاورة لها، وتتضمن الاتجاهات المسيطرة للرياح وشدتها وزمن العواصف المؤثرة، إضافة إلى دراسة الوضع الجغرافي والطبوغرافي للشاطئ والمسطح المائي البحري المدروس. يسمح بناء حقل أمواج لمنطقةٍ ما، بإنشاء بنك معلومات حقلية خاصة بأنظمة التموج، ويساعد على رفد بنك المعلومات بمعطيات وسجلات دائمة عن نظام التموج، يمكن الاعتماد عليها في الدراسات الحقلية، وعند تصميم المنشآت الشاطئية البحرية. تم بناء نموذج رياضي لحقل الأمواج المتشكل في المنطقة باستخدام برنامج (SMS) بنموذجيه   (ADCIRC-STWAVE)، حيث أسهم هذا النموذج في وضع خارطة لحقول الأمواج والتيارات المتشكلة ضمن فترة تكرار(50عاما) من أجل اتجاهات الرياح المسيطرة في المنطقة. كما أنه يمكن اعتماد نتائج هذا النموذج، نظراً للدقة والموثوقية التي يتمتع بها.